Antifungal activity of bioactive constituents and bark extracts of Rhododendron arboreum - Nisar, Muhammad; Ali, Sajid; Qaisar, Muhammad; Gilani, Syed Naeemuddin; Shah, Muhammad Raza; Khan, Inamullah; Ali, Gowhar (Bangladesh Journal of Pharmacology, 2013)
Rhododendron arboreum various fractions of bark as well as the isolated compounds were investigated against pathogenic fungi to provide evidence for the folkloric uses reported in the traditional system. Various solvent fractions and compounds were tested using agar well diffusion method at concentrations of 50, 25 and 12.5 mg/mL, the maximum inhibition recorded against fungi 17-32, 15-27 and 10-24 mm for methanol extract, 16-28, 14-26 and 10-22 mm to ethyl acetate extract, 17-21, 8-18 and 10-16 to chloroform extract and 8-15 and 8-12 mm to n-hexane extract respectively. Maximum inhibition at 10, 5 and 2.5 mg/mL of isolated triterpenoids was recorded against such as fungi 28-44, 25-42 and 20-40 mm for 3β-acetoxyurs-11,12-epoxy-13β,28-olide, 23-44, 20-42 and 15-40 mm for betulin and 17-40, 15-37 and 13-34 for lupeol respectively. It is concluded from the present study that the antifungal activity of the extracts may be due to the presence of 3β-acetoxyurs-11,12-epoxy-13β,28 - olide, betulin, lupeol and taraxerol.